2015
DOI: 10.1111/eva.12250
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and natural drivers of gene flow in a temperate wild fruit tree: a basis for conservation and breeding programs in apples

Abstract: Gene flow is an essential component of population adaptation and species evolution. Understanding of the natural and anthropogenic factors affecting gene flow is also critical for the development of appropriate management, breeding, and conservation programs. Here, we explored the natural and anthropogenic factors impacting crop-to-wild and within wild gene flow in apples in Europe using an unprecedented dense sampling of 1889 wild apple (Malus sylvestris) from European forests and 339 apple cultivars (Malus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 56 publications
11
84
6
1
Order By: Relevance
“…More problematic is the possibility of genetic swamping of the wild progenitor populations ( e.g. , Martínez-Castillo et al 2008; Cornille et al 2015; Fuchs et al 2016), which, in the case of Malaysian O. rufipogon , are increasingly rare and have no in situ conservation status. Introgression from cultivated rice into weedy rice is not uncommon (Xia et al 2011; Ellstrand et al 2013; Jiang et al 2012), and the recent widespread adoption of herbicide-resistant rice production will likely increase hybridization due to selection for introgression of resistance alleles into weed populations (Burgos et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…More problematic is the possibility of genetic swamping of the wild progenitor populations ( e.g. , Martínez-Castillo et al 2008; Cornille et al 2015; Fuchs et al 2016), which, in the case of Malaysian O. rufipogon , are increasingly rare and have no in situ conservation status. Introgression from cultivated rice into weedy rice is not uncommon (Xia et al 2011; Ellstrand et al 2013; Jiang et al 2012), and the recent widespread adoption of herbicide-resistant rice production will likely increase hybridization due to selection for introgression of resistance alleles into weed populations (Burgos et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…vinifera and V. vinifera subsp. sylvestris ) [3, 4] and apples ( Malus domestica and M. sylvestris ) [5]. In addition to gene flow, dispersal of seeds from cultivated trees into natural surroundings can result in feral populations of natural aspect [6], as shown for several plants introduced to Australia, including Olea europaea [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…On this background, knowledge of the status of naturally growing populations of olives is of high importance for developing conservation programs for this valuable germplasm. Conservation efforts should also address the risks of hybridization and introgression from domesticated crops into populations of their wild relatives [32], as recently shown for fruit trees [2, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Crop-to-wild gene flow has been considered a threat to natural genetic resources and has received particular attention in recent decades. In fruit trees, introgression from cultivars to wild populations has been investigated and shown to be widespread (Cornille et al, 2015, and references therein). For example, crop-to-wild gene flow was shown to be responsible for a decrease in fitness in apple wild populations, leading researchers to consider non-introgressed populations with high levels of genetic diversity as a priority for conservation programmes (Bleeker et al, 2007;Cornille et al, 2015).…”
Section: Implications For Conservation and Use Of O Sylvestris Genetmentioning
confidence: 99%
“…In fruit trees, introgression from cultivars to wild populations has been investigated and shown to be widespread (Cornille et al, 2015, and references therein). For example, crop-to-wild gene flow was shown to be responsible for a decrease in fitness in apple wild populations, leading researchers to consider non-introgressed populations with high levels of genetic diversity as a priority for conservation programmes (Bleeker et al, 2007;Cornille et al, 2015). In olive, recent studies have demonstrated frequent introgression from seed orchards and cultivated stands to wild populations (Besnard et al, 2011(Besnard et al, , 2013Perea and Gutiérrez-Gal an, 2016) showing the importance of assessing gene flow patterns when natural and cultivated stands are in close contact.…”
Section: Implications For Conservation and Use Of O Sylvestris Genetmentioning
confidence: 99%